Changes in the QT Intervals, QT Dispersion, and Amplitude of T Waves after Hemodialysis - Drighil, Abdenasser (Ann Noninvasive Electrocardiol, 2007)
Background: Increased QT dispersion (QTd) has been associated with an increased risk for ventricular arrhythmias and sudden death in the general population and in various clinical states. Methods: We investigated the impact of hemodialysis (HD) on QT, QTd, and T‐wave amplitude in subjects with end‐stage renal failure. Data on 49 patients on chronic HD were studied. The QT, QTd, and the sum of amplitude of T waves (ΣT) in millimetre in the 12 ECG leads, along with a host of other ECG parameters, body weight, blood pressure, heart rate, electrolytes, and hemoglobin/hematocrit were measured before and immediately after HD. Results: QT decreased (380.9 ± 38.4–363.5 ± 36.8 ms, P = 0.001), the QTc did not change (406.2 ± 30.8–405.4 ± 32.2 ms, P = 0.8), the QTd increased (31.3 ± 14.6–43.9 ± 18.6 ms, P = 0.003), and the ΣT decreased (32.3 ± 15.7–25.9 ± 12.6 mm, P = 0.0001) after HD. There was no correlation between the change in QTd and the changes in serum cations, heart rate, the subjects' weight, T‐wave duration, and ΣT. However, the change in QTc correlated inversely with the change in serum Ca(++) (r =−0.339, P = 0.021). Conclusion: QTd increased, the ΣT decreased, and the QTc and T‐wave duration remained stable, after HD. The QTd increase, although may be real, could also reflect measurement errors stemming from the decrease in the amplitude of T waves (as shown recently), imparted by HD; this requires clarification, to use QTd in patient on HD.